A Biocatalytic Nanomaterial for the Label‐Free Detection of Virus‐Like Particles. (3rd May 2017) - Sykora, Sabine; Correro, M. Rita; Moridi, Negar; Belliot, Gaël; Pothier, Pierre; Dudal, Yves; Corvini, Philippe F.‐X.; Shahgaldian, Patrick
Abstract: The design of nanomaterials that are capable of specific and sensitive biomolecular recognition is an on‐going challenge in the chemical and biochemical sciences. A number of sophisticated artificial systems have been designed to specifically recognize a variety of targets. However, methods based on natural biomolecular detection systems using antibodies are often superior. Besides greater affinity and selectivity, antibodies can be easily coupled to enzymatic systems that act as signal amplifiers, thus permitting impressively low detection limits. The possibility to translate this concept to artificial recognition systems remains limited due to design incompatibilities. Here we describe the synthesis of a synthetic nanomaterial capable of specific biomolecular detection by using an internal biocatalytic colorimetric detection and amplification system. The design of this nanomaterial relies on the ability to accurately grow hybrid protein‐organosilica layers at the surface of silica nanoparticles. The method allows for label‐free detection and quantification of targets at picomolar concentrations. Abstract : Onionlike nanomaterial : A complex nanomaterial combining an internal biocatalytic layer, acting as an integrated transducer system, and an external recognition layer for specific virus binding has been developed. It allows easy spectrophotometric detection of virus‐like particle targets without the use of additional labels.